INFLUENCE OF CURING ON THE PROPERTIES OF HIGH VOLUME FLY ASH CONCRETE - Naganathan, Sivakumar; Beddu, Salmia; Lau Yee Jin, Jaison; Nair, Sujendran; Kanadasan, Jegathesh (MATTER: International Journal of Science and Technology, 2017)
Fly ash concrete is the most widely used material in building construction. This is because adding fly ash in concrete reduces the cement consumption and contributes less emission. Normal constituents in concrete are cement and aggregates. Adding fly ash in concrete will enhance the performance of normal concrete. The high volume fly ash concrete is prepared at a ration of 1: 1.5: 3 cement: fine aggregate: coarse aggregate. The concrete is then kept in three different curing regimes. The concrete was then tested for its compressive strength, water absorption and initial surface absorption (ISAT). It is concluded that concrete cured under the normal water curing condition gives the best performance results.